2018
DOI: 10.2196/resprot.8229
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of a Social Media to Promote Weight Management Engagement in Adolescents with Severe Obesity: Pilot Study

Abstract: BackgroundSevere obesity in adolescents has deleterious physical and psychological complications necessitating frequent multi-disciplinary clinic visits. Greater treatment engagement has been equated with weight-loss. However, traditional medical weight-loss programs for adolescents have high attrition rates. Social media is widely used by adolescents and may enhance medical weight management engagement and success.ObjectiveThe first objective was to examine the acceptability and feasibility of using a private… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…This challenge was often acknowledged and reflected upon in our moderator interviews. Nevertheless, in a variety of instances, moderators have been perceived positively with appreciation from users while serving the roles of encouraging user participation and filtering undesired content [29-31]. In the technological usability study of SOVA, we found no concerns from users regarding moderator interactions [18].…”
Section: Discussionmentioning
confidence: 99%
“…This challenge was often acknowledged and reflected upon in our moderator interviews. Nevertheless, in a variety of instances, moderators have been perceived positively with appreciation from users while serving the roles of encouraging user participation and filtering undesired content [29-31]. In the technological usability study of SOVA, we found no concerns from users regarding moderator interactions [18].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, in a sample of 20 adolescents between the ages of 12 and 16 years with type 1 diabetes, those who used a mobile health app with a social networking component showed an improvement in blood glucose monitoring [10]. In addition, preliminary findings in a sample of 13 youth with obesity indicated that social media groups are an acceptable and effective adjunct to obesity treatment [11]. Social media as an intervention has also been used to target sexual health and tobacco cessation.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 Percebe-se também que a utilização das redes sociais voltadas para o aumento da prática de atividade física e redução da ingestão de calorias com o objetivo do controle do peso envolvendo indivíduos com sobrepeso e obesidade mostrou-se bastante agradável, com 100% dos participantes em um estudo desenvolvido nos Estados Unidos tendo afirmado que o suporte de mídia social é útil para reforçar as metas de controle de peso, além de uma fonte de motivação. 22 Detalha-se, não obstante, que outro estudo, que procurou avaliar o controle de peso por meio de um sistema de redes sociais on-line em comparação a um sistema de teleconferência, demonstrou que a perda de peso não foi significativa e os participantes não se sentiram confortáveis em compartilhar suas metas entre o grupo das redes sociais. 30 Nota-se que a não eficácia de algumas tecnologias no controle do peso pode estar associada à implantação de seus métodos para com a saúde, principalmente quando as intervenções ocorrem no âmbito escolar e com a população adolescente ou de alta pobreza.…”
Section: Discussionunclassified
“…Intervenção baseada nas mídias sociais. 22 Os participantes consideraram o suporte de mídia social agradável, útil para reforçar as metas para o controle de peso, uma fonte de motivação. Porém, reportaram a necessidade da implantação de um programa de controle de peso pessoalmente junto com o grupo de suporte de mídia social (92%; [12/13]).…”
Section: Polímeros Farmacêuticos: D I S P O S I T I V O E P I To M E Eunclassified